Plant leaf litter plays a more important role than roots in maintaining earthworm communities in subtropical plantations. (May 2020) - Chen, Yuping; Cao, Jianbo; He, Xinxing; Liu, Tao; Shao, Yuanhu; Zhang, Chenlu; Zhou, Qingqiu; Li, Feng; Mao, Peng; Tao, Libin; Liu, Zhanfeng; Lin, Yongbiao; et al.
Abstract: Despite the importance of earthworms to making soils productive, little is known regarding the relative importance of maintenance of the various types of earthworm populations. In this study, we assessed the impact of long-term removal of two potential sources of carbon input, viz. plant litter and roots, on earthworms of Amynthas sp. (epigeic) and Pontoscolex corethrurus (endogeic) that reside at and below the soil surface and primarily rely on litter and/or soil organic matter as a food source, in two different subtropical monoculture plantations. We found that Amynthas sp. disappeared and the density and biomass of Pontoscolex corethrurus was significantly reduced under litter removal treatment, whether roots were removed or not. In contrast, root removal had no significant impact on the density and biomass of both earthworm species. The results suggest that leaf litter, rather than roots, played key roles in maintaining the populations of both the epigeic Amynthas sp. and endogeic Pontoscolex corethrurus earthworms. Highlights: Effect of leaf litter on earthworm community was greater than that of roots. Amynthas sp. and Pontoscolex corethrurus were negatively affected if leaf litter was removed. Leaf litter affected Amynthas sp. through providing both habitat and food resource. Leaf litter affected Pontoscolex corethrurus mainly through providing food resources.